The Effect of CYP3A Induction and Inhibition on the Pharmacokinetics of Laquinimod, a Novel Neuroimmunomodulator. Issue 8 (1st April 2020) - Elgart, Anna; Greenblatt, David J.; Loupe, Pippa S.; Zur, Arik A.; Weiss, Sivan; Mimrod, Dorit; Spiegelstein, Ofer
Abstract: Laquinimod, a neuroimmunomodulator, is extensively metabolized by cytochrome P450 (CYP) 3A4, and modulations of CYP3A4 activity may lead to alterations in the pharmacokinetics and/or clinical effects of laquinimod. To determine the drug‐drug interaction potential of laquinimod with CYP3A inhibitors and inducers, interaction assessments were conducted in healthy volunteers using single‐dose administration of laquinimod before and after multiple dosing of CYP3A inhibitors (ketoconazole, fluconazole, and cimetidine) or a CYP3A4 inducer (rifampin). For ketoconazole, subjects (n = 14) received laquinimod 0.6 mg following 1 day of ketoconazole (400 mg daily) pretreatment, a single concomitant dose, and 28 additional days. For fluconazole, subjects (n = 14) received laquinimod 0.6 mg after a single fluconazole dose of 400 mg followed by 200‐mg daily fluconazole administration for 20 additional days. For cimetidine, subjects (n = 14) received laquinimod 0.6 mg following 1 day of cimetidine (800 mg twice daily) pretreatment, a single concomitant dose, and 21 additional days. For rifampin, subjects (n = 14) received laquinimod 0.6 mg following 9 days of rifampin (600 mg daily) pretreatment, a single concomitant dose, and 12 additional days. Coadministration of laquinimod with CYP3A inhibitors, ketoconazole, fluconazole, and cimetidine increased laquinimod area under the plasma concentration–time curve from time zero to infinity by approximately 3.1‐, 2.5‐, and 1.1‐fold, respectively. Coadministration of laquinimod with rifampin decreased laquinimod area under the plasma concentration–time curve from time zero to infinity by 5‐fold. These results indicate that coadministration of laquinimod with moderate to strong inhibitors of CYP3A or strong inducers of CYP3A may give rise to significant pharmacokinetic drug interactions.